Natural radioprotectors on current and future perspectives: A mini-review - Pooja Shivappa; Grisilda Vidya Bernhardt (Wolters Kluwer Medknow Publications, 2022)
Radiation therapy is used as the primary treatment for cancer. Eighty percent of cancer patients require radiation therapy during treatment or for medical purposes. During treatment, radiation causes various biological defects in the cells. The prevalence of cytotoxicity limits the dose used for effective treatment. This method is designed to strike a balance between removing cancer cells and protecting normal tissues. Unfortunately, effective radiation is unavailable once acute toxicity occurs during clinical radiation therapy. Therefore, a lot of research interest is needed in the discovery of radioprotective drugs to accelerate treatment to reduce this toxicity (i.e., normal tissue toxicity to cancer cell death). Radiation protectors may be chemicals or drugs that minimize the damage caused due to radiation therapy in living organisms. The determination of effective and nontoxic radiation protection is an essential goal for radiation oncologists and basic radiobiologists. However, despite the advantages, many radioprotectors were found to have disadvantages which include cost, less duration, toxicity, and effect on the central nervous system. Therefore in recent years, the focus has been diverted to finding out optimal natural products to act as radioprotectors. Natural radiation protectors are plant compounds that protect normal (noncancerous) cells from damage from radiation therapy. Natural herbal products are nontoxic with proven therapeutic benefits and have long been used to treat various diseases. In conclusion, we find that there are various radiation protectors with different purposes and mechanisms of action.